Sabhara Kudus Police Unit Effort In Combating Adulterated Liquor In Kudus District - Deni Dwi Noviandi; Aryani Witasari (Jurnal Daulat Hukum, 2018)
The issues of law enforcement in combating adulterated liquor in the Kudus Police Region, There are two (2) ways circulation of liquor law enforcement carried out by the Sabhara Kudus Police unit, namely preventive and repressive. As for preventive measures carried out where possible and still their awareness to obey the law. While repressive action is action taken if preventive measures are not effective, so that the people carrying out the law though involuntarily. While the police in law enforcement there are (two) action that is persuasive and repressive action which has its own purpose.Constraints faced by the Sabhara Kudus Police Unit in combating adulterated liquois related to the limited number of Members of the unit Sabhara Police at the sanctuary that is generally still not satisfactory, not maximum, and uneven steps socialization PERDA (Regional Regulation) conducted at the societal level, so far not uncommon understanding less precise with regard to the procedures or systems at the time of preparation until the determination of regulation efforts Sabhara Police Unit in combating Kudus adulterated liquor in the Kudus Police Region. Effort or attempt Sabhara Police Unit of the Kudus in minimizing the violation is by way of non-judicial and pro justicia. Non-judicial action is accomplished by providing guidance, exhort or guide in order not to repeat the mistakes that have been made that violates local laws. If this action is less provide a deterrent effect and the parties related to underestimate, then the action pro justicia, the actions of pro justicia is taken when actions coaching or non judicial considered insufficient because only given guidance only, then Sabhara Kudus Police Unit may soon crack down and will be brought to trial and be subjected to probation.Keywords: Sabhara Kudus Police Unit ;  Adulterated liquor.